Morphology of vascular ring arch anomalies influences prognosis and management. Issue 5 (26th October 2020) - Ctori, Elena; Crucean, Adrian; Pinkey, Benjamin; McGuirk, Simon P; Anderson, Robert H; Stickley, John; Jones, Timothy J; Seale, Anna N
Abstract : Objective: This study aimed to explore the anatomical features of aortic arch anomalies associated with vascular rings, hoping to identify those which may increase the risk of symptomatic presentation and surgical intervention. Methods: This was a retrospective observational study at a single cardiac unit. Individuals diagnosed with an aortic arch anomaly, either isolated or non-isolated, between June 2014 and September 2018 were included. The morphology of the aortic arch was established via analysis of postnatal echocardiography, CT or MRI scans. CT and magnetic resonance studies were evaluated for the presence of a Kommerell diverticulum in those with aberrant vessels. Case notes were reviewed for relevant clinical data. Results: Of those with aberrant subclavian arteries, 24/79 (30.4%) were shown to have a Kommerell diverticulum. Additional forms of congenital heart disease were present in 133/227 (58.6%) individuals. Surgical division of the vascular ring was performed in 30/227 (13.2%), most commonly in the setting of a double aortic arch (70.8%). In those with aberrant subclavian arteries, no children without a Kommerell diverticulum were referred for surgery. In those with a Kommerell diverticulum confirmed on imaging, 11/24 underwent surgery. Conclusion: Individuals with a double aortic arch, or an aberrant subclavian artery arising from a Kommerell diverticulum, have the highest requirement for surgical intervention, especially in isolated anomalies. These individuals should remain under monitoring. The subjective nature of symptoms remains problematic. Longitudinal research is required further to understand the natural history of vascular rings and how it links to morphology.